2017
DOI: 10.1159/000457945
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Oxidative Stress-Induced Osteoblast Apoptosis by Curcumin is Associated with Preservation of Mitochondrial Functions and Increased Akt-GSK3β Signaling

Abstract: Background: Osteoblast apoptosis induced by oxidative stress plays a crucial role in the development and progression of osteoporosis. Curcumin, a natural antioxidant isolated from Curcuma longa, has highly protective effects against osteoporosis. However, the effects of curcumin on oxidative stressinduced osteoblast apoptosis remain unclear. This study aimed to explore the effect of curcumin on hydrogen peroxide (H 2 O 2 ) induced osteoblast apoptosis and the underlying mechanisms. Methods: An osteoblastic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 56 publications
5
74
1
Order By: Relevance
“…It has been revealed that antioxidant-based dietary approach is beneficial to osteoporosis prevention and treatment in Brazilian women (De Franca et al, 2013). In addition, attenuation of H 2 O 2 stimulation increases osteoblasts viabilities and differentiation (Yan et al, 2017) through improving the mitochondrial redox homeostasis and functions (Dai et al, 2017). Elimination of ROS generation inhibits bone resorption through receptor activator of nuclear factor κB (NF-κB) ligand (RANKL) mediated NF-κB activation (Thummuri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that antioxidant-based dietary approach is beneficial to osteoporosis prevention and treatment in Brazilian women (De Franca et al, 2013). In addition, attenuation of H 2 O 2 stimulation increases osteoblasts viabilities and differentiation (Yan et al, 2017) through improving the mitochondrial redox homeostasis and functions (Dai et al, 2017). Elimination of ROS generation inhibits bone resorption through receptor activator of nuclear factor κB (NF-κB) ligand (RANKL) mediated NF-κB activation (Thummuri et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, a natural versatile compound from Curcuma longa , has been shown to improve the mitochondrial functions, decrease mitochondrial oxidative stress, and prevent cell apoptosis through activation of Akt/GSK-3β signaling in Saos-2 cells [80]. Resveratrol, the most famous polyphenol, significantly alleviates MPP+-induced mitochondrial dysfunctions through activation of Akt-GSK-3β signaling in SN4741 cells [81].…”
Section: Natural Compounds Regulate Mitochondrial Activity Through Gsmentioning
confidence: 99%
“…Measurement of RVLM protein was performed as previously described [28,30]. Briefly, protein extracted from the RVLM was used for measurements of TNF-α, the 67-kDa isoform of glutamate decarboxylase (GAD67), atrial natriuretic peptide (ANP), beta-myosin heavy chain (β-MHC), NAD(P)H oxidase subunit NOX 2 (gp91 phox ) and NOX 4 (Santa Cruz Biotechnology Inc, Santa Cruz, California) expressions by western blot.…”
Section: Western Blottingmentioning
confidence: 99%